Proceedings of the Eighteenth ACM SIGSOFT International Symposium on Foundations of Software Engineering 2010
DOI: 10.1145/1882291.1882297
|View full text |Cite
|
Sign up to set email alerts
|

Finding latent performance bugs in systems implementations

Abstract: Robust distributed systems commonly employ high-level recovery mechanisms enabling the system to recover from a wide variety of problematic environmental conditions such as node failures, packet drops and link disconnections. Unfortunately, these recovery mechanisms also effectively mask additional serious design and implementation errors, disguising them as latent performance bugs that severely degrade end-to-end system performance. These bugs typically go unnoticed due to the challenge of distinguishing betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Following the convention of developers and researchers on this topic [5,26,40,50], we refer to performance bugs as software Performance bugs exist widely in released software. For example, Mozilla developers have fixed 5-60 performance bugs reported by users every month over the past 10 years.…”
Section: Motivationmentioning
confidence: 99%
“…Following the convention of developers and researchers on this topic [5,26,40,50], we refer to performance bugs as software Performance bugs exist widely in released software. For example, Mozilla developers have fixed 5-60 performance bugs reported by users every month over the past 10 years.…”
Section: Motivationmentioning
confidence: 99%
“…Previous studies have shown that this type of performance-related software defects 1 widely exist in real-world [10,21,24,35,41]. They are difficult for developers to avoid due to the lack of performance documentation of APIs and the quickly changing workload of modern software [21].…”
Section: Motivationmentioning
confidence: 99%
“…Previous study has shown that this type of performance-related software defects 1 widely exist in real- 1 We will refer to these defects as performance bugs or performance problems interchangeably following previous work in this area [18,21,30]. world [9,18,21,28,34].…”
Section: Motivationmentioning
confidence: 99%